Edu sains - Institut Agama Islam Negeri Palangka Raya (Institut Agama Islam Negeri (IAIN) Palangka Raya, 2013)
Science and mathematics education, teaching and learning.
Keywords: Science : Study and teaching : Indonesia : Periodicals; Science : Study and teaching : Periodicals; Mathematics : Study and teaching : Indonesia : Periodicals; Mathematics : Study and teaching : Periodicals; Science : Study and teaching; Mathematics : Study and teaching; Indonesia